Studi literatur: Analisis Beban Kerja Dengan Metode Full Time Equivalent (FTE) - Cahyani, Rusnandari Retno (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2024)
Workload analysis is human resource planning which aims to determine energy needs so that organizational goals can be achieved. The number of available employees exceeds actual needs, and this can disrupt employee productivity. Therefore, objective workload measurements are needed based on real conditions in the field. Various methods can be used to analyze workload targets, but this research aims to review the literature on workload analysis for the Full Time Equivalent (FTE) method. The method used for the database search used was Google Scholar from 2019 to 2023.